KONTRIBUSI STUDI ISLAM DALAM KAJIAN AL-QUR'AN DAN KANONISASINYA: Pendekatan Interdisipliner Untuk Memperluas Cakrawala Keilmuan - Istajib, Istajib; Nurhaidah, Siti Nuri; Haris Hakam, Muhammad; Mujiadi, Mujiadi (Moderation | Journal of Islamic Studies Review, 2024)
This research is expected to be able to make a meaningful contribution to the treasures of Islamic studies, especially in the framework of the study of the Qur'an. This research also aims to bridge theories that carry the theme of canonization of the Qur'an. Through an interdisciplinary approach, this study seeks to open a wider horizon of thinking, build a scientific paradigm across disciplines and religions, and motivate subsequent studies that are expected to complement the shortcomings of this research. At a practical level, this research is expected to provide new views and encourage the development of further studies that are more comprehensive and integrative in understanding the process of canonization of the Qur'an and its implications for Islamic studies. In addition, this study also seeks to identify and analyze various historical, social, and cultural factors that influence the canonization of the Qur'an. It is hoped that the results of this research can be an important reference for academics, researchers, and practitioners in developing more in-depth and extensive studies on the Qur'an. This research is also expected to enrich scientific literature and make a significant contribution to cross-cultural and religious dialogue, as well as strengthen understanding of the dynamics and complexity in the process of canonization of the Qur'an.